2011
DOI: 10.1002/hep.24349
|View full text |Cite
|
Sign up to set email alerts
|

Lack of de novo phosphatidylinositol synthesis leads to endoplasmic reticulum stress and hepatic steatosis in cdipt-deficient zebrafish

Abstract: Hepatic steatosis is the initial stage of non-alcoholic fatty liver disease (NAFLD) and may predispose to more severe hepatic disease, including hepatocellular carcinoma. Endoplasmic reticulum (ER) stress has been recently implicated as a novel mechanism that may lead to NAFLD, although the genetic factors invoking ER stress are largely unknown. During a screen for liver defects from a zebrafish insertional mutant library, we isolated the mutant cdipthi559Tg/+ (hi559). CDIPT is known to play an indispensable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 38 publications
7
83
1
Order By: Relevance
“…There appears to be no other gene for PtdIns synthesis, so the association of the enzyme activity with PM fractions may be related to their contamination with ER or with the lighter mobile PIS membrane compartment (796). Two studies reported defects in PIS activity in zebrafish, one describing ER stress and hepatic steatosis (1547), while the other observed lens structural defects and reduced number of photoreceptors (1098).…”
Section: Phosphatidylinositol Synthesismentioning
confidence: 99%
“…There appears to be no other gene for PtdIns synthesis, so the association of the enzyme activity with PM fractions may be related to their contamination with ER or with the lighter mobile PIS membrane compartment (796). Two studies reported defects in PIS activity in zebrafish, one describing ER stress and hepatic steatosis (1547), while the other observed lens structural defects and reduced number of photoreceptors (1098).…”
Section: Phosphatidylinositol Synthesismentioning
confidence: 99%
“…This conservation of function and the absence of fasting steatosis in larvae that have never been fed (Schlegel and Stainier 2006) allowed us to screen for mutations causing increased hepatic lipid mass. Performing the screen in animals carrying three transgenes that encode fluorescent protein labels of the Islet of Langerhans b cells, the liver hepatocytes, and the pancreatic acinar cells (Anderson et al 2009) helped us to avoid mutants that displayed changes in liver or pancreas morphology (Sadler et al 2005;Akimitsu et al 2008;Matthews et al 2009;Thakur et al 2011). Defects in yolk lipid transport were avoided by restricting our analysis to only larvae that consumed all their yolk by 6 d post-fertilization (dpf) (Schlegel and Stainier 2006;Raldú a et al 2008;Walters et al 2009).…”
mentioning
confidence: 99%
“…CDP-diacylglycerol-inositol 3-phosphatidyltransferase (CDIPT) deficiency increases endoplasmic retuculim stress, leading to hepatic steatosis Gastro-intestinal HI559, CDIPT [136] After 1-week fasting, zebrafish show unaltered leptin-a levels but reduced leptin-b [107]. In goldfish, a different teleost fish species, leptin injections suppress appetite via inhibiting the NPY signaling pathways [108].…”
Section: Gastro-intestinalmentioning
confidence: 99%